VISUALIZING THE CULTURAL HERITAGE OF MALAY SOCIETY BASED ON MAPS IN TEBO REGENCY, JAMBI PROVINCE (Malay Studies: History, Culture and Civilization, 2025)
Abstract: This study explores the cultural heritage of the Malay society in Tebo Regency, Jambi Province, through the lens of geospatial visualization. The primary purpose of the research is to document and analyze the distribution of traditional practices and cultural values geographically to promote cultural preservation and understanding. Using a qualitative and quantitative approach, the study integrates primary data collected from field observations and interviews with secondary sources such as cultural records and geographic data. GIS technology is employed to create a cultural map that visually represents traditional ceremonies, dances, and rituals unique to the region. Key findings reveal significant patterns in the spatial distribution of cultural practices, highlighting areas with rich cultural activity and their ecological and historical contexts. The research underscores the potential of maps as powerful tools for cultural education and promotion, as well as their role in safeguarding local traditions against modernization pressures. This work contributes to the broader discourse on cultural preservation by demonstrating the value of interdisciplinary approaches in heritage studies. Keywords: cultural heritage, Malay society, geospatial visualization, GIS, Tebo Regency